Effect of mangosteen peel extract (Garcinia mangostana L.) supplementation on the in vitro gas kinetics, degradability, and intestinal digestion of proteins using a three-step in vitro procedure - Sonthongdaeng, Chutikan; Foiklang, Suban; Cherdthong, Anusorn; Paserakung, Anon; Laorodphan, Norakamol (Frontiers in Animal Science, 2025)
This study aimed to investigate the effect of tannin extract from mangosteen peel (MANGTAN) in soybean meal on the in vitro gas production kinetics, degradability, and intestinal digestion of proteins using a three-step in vitro procedure. A completely randomized design (CRD) was used as the experimental design with nine treatments. The dietary treatments involved spraying different amounts of mangosteen peel extract (MANGTAN; mL) onto soybean meal (SBM; gDM) in a mixture, with the ratios being 0:100, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, and 40:100. It was found that MANGTAN did not influence the gas production kinetics (P < 0.05). However, MANGTAN did influence the gas production from the immediately soluble fraction (a), which was found to have the highest gas volume at the level of 15 mL of MANGTAN/100 gDM of soybean meal. In vitro dry matter at 12 h decreased when using 5–40 mL of MANGTAN/100 gDM of soybean meal. Organic matter degradability at 12 and 24 h was reduced when using MANGTAN on soybean meal (P < 0.05). Analysis of crude protein degradability using a three-step in vitro procedure found that increasing the levels of 5 to 40 mL of MANGTAN/100 gDM of soybean meal resulted in reduced crude protein degradation in the rumen (24 h), but the intestinal digestion of proteins was improved. In addition, the levels of 15 mL of MANGTAN/100 gDM of soybean meal and above influenced the decrease in total protein degradation (P < 0.05). Based on the results, using 15 mL of MANGTAN/100 gDM of soybean meal could modify gas production kinetics, increase in vitro degradability, protect ruminal crude protein degradability, and increase intestinal crude protein degradability.